Preservation Efficacy of Tris-egg Yolk-glucose Extender for Motility, Viability, Morphology and Membrane Integrity of Canine Semen during Refrigerated Storage at 4°C - Meena, Abhay Kumar; Saraswat, Chandra Shekhar; Yadav, Sumit Prakash (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during the months from July to September, 2022 at the Department of Veterinary Gynaecology and Obstetrics, Post Graduate Institute of Veterinary Education and Research (PGIVER), Jaipur. The objective of this study was to determine the effect of a Tris-Egg Yolk-Glucose Extender on the quality parameters of dog semen (n=24 ejaculates) during refrigeration (4°C) preservation up to 72 hours. Semen was collected from six male dogs, with four ejaculates obtained per animal using digital manipulation. Each fresh ejaculate underwent thorough macroscopic assessments (including volume, colour, consistency and pH) and microscopic analyses to evaluate sperm motility, morphology, viability and Membrane Integrity. The semen samples were then extended in a Tris-Egg Yolk-Glucose using a split sample technique. The diluted semen was kept in a refrigerator for preservation at 4°C and evaluated at 0, 24, 48, and 72 hours for sperm quality parameters. There was a significant difference (p<0.05) in sperm motility percentage at different time slots of preservation. The sperm motility significantly reduced over a period of time from 0 to 72 hours within Tris-Egg Yolk-Glucose Extender. The live sperm percentage was numerically higher in the TRIS-Egg yolk-glucose dilutor at 24, 48, and 72 hours but lower at 0 hours. The percentages of morphologically abnormal spermatozoa were numerically lower at 0, 24, 48, and 72 hours of storage. There was no significant difference in intact plasma membrane percentage at 0, 24 hours and a significant difference in intact plasma membrane percentage at 48, 72 hours was computed.